"Gambling With My Cards Face Up": Vulnerability as a Risky Act Among Men. Issue 2 (June 2022) - Durón Delfín, Florencia; Leach, Rebecca B.
This study examines men's lived experiences of suppressing vulnerability in a conflict. These moments of suppression happened during conflicts with friends, romantic partners, or family members. A phronetic-iterative approach guided an in-depth analysis of 16 qualitative interviews to illuminate the social conditions and expectations that prevented men from verbally expressing vulnerability. Men made sense of their own and others' suppression patterns by naming cultural, relational, and individual factors. We argue that the toxic culture of masculinity is constructed collectively, such that men's communication creates and reinforces expectations of what it means to be "strong" men. Reshaping the current culture into a safe space for men to express emotions will require intentional efforts from both men and their support systems.